Safeguarding Australians : mapping the strengths and challenges toward sustainable improvements in OHS education and practice. - Toft, Yvonne; Capra, Mike; Moodie-Bain, Debra; Kift, Ryan; Pryor, Pam; Eddington, Ian; Joubert, Darren (Australian Learning and Teaching Council, 2010)
The broad aim of Safeguarding Australians was to facilitate alignment of Occupational Health and Safety (OHS) education with evolving workforce requirements. With a focus on education of the generalist OHS professional, the project was informed by current issues in OHS education, including: lack of an agreed core body of knowledge for OHS; lack of clarity regarding the required level of education for an OHS professional; appropriateness of current teaching strategies for equipping OHS professionals for operation in a changing business environment; appropriateness of external modes of delivery of OHS programs; availability of suitably qualified OHS educators; and preparation of OHS professionals to be lifelong learners. Literature relevant to education of the generalist OHS professional was reviewed with thematic attention on integrity of the profession, student learning and the OHS academy.' The investigation strategy was geared to facilitating extensive consultation with OHS professional, regulator, educator, registered training organisation and graduate stakeholders. Action research methodology allowed a cyclic multi-phase process of data collection and analysis, with ongoing refinement of survey instruments. Various combinations of stakeholder groups were included in focus group discussions, surveys, telephone interviews and a workshop. [Executive summary, ed]